Mapping the Growth Potential of Culinary MSMEs in West Java Regencies and Cities Using Open Government Data-Based K-Means Clustering - Leonardo Ernesto Meba; Rahma Wahdiniwaty; Satvaldiyeva Nilufar Zoyirjonovna (Universitas Komputer Indonesia, 2026)
Culinary MSMEs play an important role in entrepreneurship and regional economic development in areas having diverse markets and tourism potentials. The development of culinary MSMEs in various regencies and cities in West Java is uneven, emphasizing the necessity of data-driven mapping in order to precisely determine the growth potential of the regions. This paper seeks to classify the growth potential of culinary MSMEs in West Java regencies and cities using K-Means Clustering based on open government data. The data used in this paper were taken from Open Data Jawa Barat and consist of the number of projected MSMEs by regency or city and business category for 2017-2023. There were six research steps carried out in this study: data selection, data preprocessing, data transformation, data normalization, clustering, and cluster result interpretation. It was found that there were 27 regencies and cities classified into three different clusters, namely 12 regions having high potential, 14 regions having moderate potential, and one region having low potential. It can be seen that there was relatively similar percentage growth in all regions, at 43.36%. This research implies that regions that have bigger MSME clusters should have strategies for competitiveness and expansion of their markets, whereas lower potential regions would benefit from having more basic entrepreneurship strategies. This paper demonstrates that using the K-Means Clustering approach and open government data can be a useful tool for making decisions.